Dilemma of Public Governance (administration) Reform in the RA (paradigm approach) - Minasyan, Karine (Bulletin of Yerevan University G: Economics, 2022)
The main purpose of the article is unfolding discussion and formulation of the problem of choosing the basic paradigm of public administration in Armenia at the present stage of reforms. Using the approaches of the securitization theory developed at the Copenhagen School, highlighted three main existential threats facing Armenia: a military threat, threats associated with a change in the economic pattern (mode) and the threats of loss of national identity. The described paradigms of public administration (administration) and the analysis of modern approaches to reforming public administration in different regions shows, that the choice of the paradigm of public administration should proceed from the understanding and prioritization of the existential threats facing the state. The task becomes more complicated, as different threats require different specific approaches in public administration and the state faces a dilemma of choice. Moreover, approaches to digital transformation in public sector and, accordingly, the chosen basic model of public administration fundamentally depend on the prioritization of threats. The approach proposed in the article requires the state authorities to rethink and significantly refine the proposed package of public administration reforms, presented for discussion to a wide range of the public. This will significantly increase effectiveness and performance of reforms.